2003
DOI: 10.1002/prop.200390001
|View full text |Cite
|
Sign up to set email alerts
|

On the absence of large‐order divergences in superstring theory

Abstract: The genus‐dependence of multi‐loop superstring amplitudes is estimated at large orders in perturbation theory using the super‐Schottky group parameterization of supermoduli space. Restriction of the integration region to a subset of supermoduli space and a single fundamental domain of the super‐modular group suggests an exponential dependence on the genus. Upper bounds for these estimates are obtained for arbitrary N‐point superstring scattering amplitudes and are shown to be consistent with exact results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…and it has been demonstrated that the products Q 0 j1 K 1=2 j and Q 0 j1 ÿ K 1=2 j are exponential functional of the genus [5], the sum (4.1) is bounded by the product of an exponential and…”
Section: Estimates Of the Supermoduli Space Integralmentioning
confidence: 99%
See 1 more Smart Citation
“…and it has been demonstrated that the products Q 0 j1 K 1=2 j and Q 0 j1 ÿ K 1=2 j are exponential functional of the genus [5], the sum (4.1) is bounded by the product of an exponential and…”
Section: Estimates Of the Supermoduli Space Integralmentioning
confidence: 99%
“…While a minimum-length condition is satisfied by the categories of isometric circles [4] i 0 g 1ÿ2q 0 jK n j the sizes of the handles decrease to zero even in the intrinsic metric in the following ranges for the parameters [5] 0 n q 00 jK n j 0 0 n q 00 ; q 00 > 1; n 1; 2; 3; . .…”
Section: Introductionmentioning
confidence: 99%
“…13 Given that the first two sectors are chosen to be the Neveu-Schwarz and Ramond sectors, the remaining spin structures can be obtained from modular transformations of S 1 and S 2 . While it has not been established whether there exists a set of 2 g − 2 transformations which generates the 2 2g spin structures without any overlaps, it has been found that there is a set of 3 g − 2 g − 1 modular transformations {ρ r }, with S 1 = S ′ 1 ,…”
Section: (523)mentioning
confidence: 99%
“…13 Although there is a quotient by a factorial for each value of q, the values of q for isometric circles can be chosen such that the maximum contribution would have an exponential dependence of the genus, since there is a factor of g g arising from the fixed point integrals, except from the first category defined in Sec. 2.…”
Section: S Davismentioning
confidence: 99%
“…This exponential growth resembles the upper bound for the scattering amplitudes of superstring theory [12,13]. A proof of this conjecture requires an analysis of the maximum magnitude of the coefficients for convex and starlike functions on the superdisk.…”
Section: The Supersymmetric Generalizationmentioning
confidence: 99%